WORK ETHIC, WORK DISCIPLINE, AND EMPLOYEE PERFORMANCE: EMPIRICAL EVIDENCE FROM MANUFACTURING COMPANIES - Enawar Enawar (Dynamic Management Journal, 2026)
This study investigates the influence of work ethic and work discipline on employee performance, a critical area in human resource management due to its direct impact on organizational effectiveness. The urgency of this research lies in the need for companies to understand the key behavioral drivers that can be leveraged to enhance workforce productivity in a competitive business environment. The primary objective was to analyze the partial and simultaneous effects of these two factors on performance. A quantitative approach was employed, utilizing a survey method with a saturated sampling technique, involving all employees of PT. Tatimel Maitoya as respondents. Data were collected through a Likert-scaled questionnaire and analyzed using multiple linear regression. The findings reveal that both work ethic and work discipline have a positive and significant effect on employee performance, both individually and collectively. This research contributes empirically to the body of knowledge in human resource management by confirming the synergistic role of these motivational and regulatory factors in shaping employee outcomes. The novelty of this study is its integrated examination of these two specific variables within the unique industrial context of PT. Tatimel Maitoya, providing a practical model for performance improvement.